Competition effect on innovation and productivity - The Portuguese case - Santos, Anabela (2019)
The aim of the present paper is to assess the effect of competition on innovation (patent applications) and on productivity (Total Factor Productivity and Labour Productivity), using data from 654 Portuguese firms, according to 208 NACE 4-digits sectors, and over the period 2007 to 2015. For this purpose, two different methodological approaches were used, a Poisson regression model for the patent function and a log-log fixed effect model for the productivity function. The results reveal that, on average, competition has a negative, U-shaped form effect on innovation in the short term, and a positive effect in the medium-long term. Nevertheless, the model focusing only on manufacturing sectors shows some differences from the model considering all economic activities, namely a linear positive effect of competition on innovation. Concerning the effect of competition on productivity, a positive effect on Total Factor Productivity emerged from the analysis, while for labour productivity a negative one prevails.